Giving primacy to the voices of people affected by cancer (PABC) in shaping educational innovations—An exploratory qualitative study. Issue 5 (23rd May 2019) - Anstey, Sally; Hale, Rachel; Ryan, Jane; Tyler, Helen; Girt, Eleri; Radley, Lesley; Nathan, Martina; Job, Claire; Chivers, Erica; Cleves, Anne; Tish, Sam; Gould, Dinah
Abstract: Background: The number of adults diagnosed with cancer is increasing. Life beyond cancer poses many challenges for individuals and their families; many of those challenges are characterised by health uncertainties both physical and emotional. Evidence suggests that appropriate education improves care and patient outcomes specifically reducing the long‐term adverse effects of cancer and its treatments and increasing adjustment. Less evidence exists as to how meeting holistic rehabilitation needs, monitoring those surviving cancer long‐term, and supporting self‐management are enabled by health care professional (HCP) education. Aims: The aims of this study were to explore the experiences of people affected by cancer (PABC) as a long‐term condition and to use the themes emerging from their experiences to develop online bespoke educational resources/tools. Methods and Results: A project team of professionals and PABC worked together on a qualitative study to explore the challenges and consequences of life beyond cancer. This paper presents the data from the exploratory focus group, analysed using thematic analysis to identify both common and unique perspectives in PABC experiences. Four themes were identified: the meaning of "survivorship"; the impact of cancer; long‐term needs/expectations; and the role of HCPs and education in meeting needs. These themes were compared with existing literature to enable understanding and "sense making" of the participants' life beyond cancer and to inform the development of the educational resources based on a fictitious patient story to be presented in a future publication. Conclusions: Derived from the PABC stories, a scripted story digitally recorded has been embedded with information and resources. Consultation with additional patient, professional, and public groups helped develop the work into an educational module for nurses and allied health care professionals.